Assessment of adherence to drug treatment and affecting factors among hypertensive patients - Yakar, Burkay; Karaca, Asli Azakoğlu; Önalan, Erhan (My University, 2019)
Introduction: Adherence to antihypertensive therapy is important for blood pressure control. Poor adherence to antihypertensive drug therapy leadsto the development of hypertensive complications and increase risk of cardiovascular events. The aim of this study was to assess adherence toantihypertensive drug therapy and associated factors among hypertensive patients.Methods: A cross-sectional study was conducted on a simple random sample of 242 patients at the Family Health Center. Adherence toantihypertensive treatment was assessed using the Turkish Modified Morisky Scale (TMMS). The factors affecting the adherence to treatment wereobtained with a sociodemographic questionnaire. Blood pressures of all participants were measured from both arms and the mean values were recorded.Results: The mean age of the 242 participants was 60.95 ± 12.54 years. Mean systolic blood pressures of the participants were 139.08±20.78 mmHgand mean diastolic blood pressures were 83.63±11.88 mmHg. Adherence to antihypertensive medication was found 76.9% (non-adherence to treatmentwas 23.1%) and 75.6% of the participants had sufficient knowledge antihypertensive treatment.Conclusions: We found numbers of drugs taken daily, level of knowledge about treatment and level of education to be the strongest factors affectingadherence to anti-hypertensive medication among our patients. We also found that high adherence to treatment is important for effective blood pressurecontrol. Health workers' questioning the adherence to antihypertensive drug therapy may provide more effective blood pressure control in hypertensivepatients.
Keywords: Genel ve Dahili Tıp